Aggregation-induced emission enhancement (AIEE) of tetrarhenium(i) metallacycles and their application as luminescent sensors for nitroaromatics and antibiotics. Issue 7 (24th January 2023) - Nurnabi, Mohammad; Gurusamy, Shunmugasundaram; Wu, Jing-Yun; Lee, Chung-Chou; Sathiyendiran, Malaichamy; Huang, Sheng-Ming; Chang, Che-Hao; Chao, Ito; Lee, Gene-Hsiang; Peng, Shie-Ming; Sathish, Veerasamy; Thanasekaran, Pounraj; et al.
Abstract : Luminescent nanoaggregates of Re(i ) metallacycles were used as potential probes for the sensitive and selective detection of explosives and antibiotics that contain nitro groups. Abstract : The self-assembly of tetrarhenium metallacycles [{Re(CO)3 }2 (μ-dhaq)(μ-N–N)]2 (3a, N–N = 1, 3-bis(1-butylbenzimidazol-2-yl)benzene; 3b, N–N = 1, 3-bis(1-octylbenzimidazol-2-yl)benzene), (H2 -dhaq = 1, 4-dihydroxy-9, 10-anthraquinone) and [{Re(CO)3 }2 (μ-thaq)(μ-N–N)]2 (4, N–N = 1, 3-bis(1-butylbenzimidazol-2-yl)benzene), (H2 -thaq = 1, 2, 4-trihydroxy-9, 10-anthraquinone) under solvothermal conditions is described. The metallacycles 3a, b and 4 underwent aggregation-induced emission enhancement (AIEE) in THF upon the incremental addition of water. TEM images revealed that metallacycle 3a in a 60% aqueous THF solution formed rectangular aggregates with a wide size distribution, while a 90% aqueous THF solution resulted in the formation of a mixture of nanorods and amorphous aggregates due to rapid and abrupt aggregation. UV-vis and emission spectral profiles supported the formation of nanoaggregates of metallacycles 3a, b and 4 upon the gradual addition of water to a THF solution containing metallacycles. Further studies indicated that these nanoaggregates were excellent probes for the sensitive and selective detection of nitro group containing picric acid (PA) derivatives as well as antibiotics.